Corporate Governance, Corporate Social Responsibility and Zakat Transparency in Islamic Financial Institutions: A Bibliometric Network Analysis - Rizky Indra Saputra; Suginam Suginam; Azwansyah Habibie (Graha Mitra Edukasi, 2025)
This study investigates the intellectual development of research on corporate governance, corporate social responsibility (CSR), and zakat transparency within Islamic financial institutions through a bibliometric network analysis. The study aims to map publication trends, influential sources, collaboration patterns, thematic evolution, and emerging research directions in the field. A bibliometric approach combined with the PRISMA framework was employed to ensure a systematic and transparent research process. Data were collected from the Scopus database using the search query related to zakat transparency and governance, resulting in 30 relevant publications published between 2010 and 2025. The analysis was conducted using publication performance indicators, co-word analysis, co-citation analysis, collaboration networks, thematic evolution, and keyword dynamics. The findings reveal a significant increase in scholarly attention after 2021, with 66.7% of publications appearing during 2024–2025, indicating that zakat transparency has become an increasingly important topic in Islamic economics and social finance. Governance, transparency, accountability, and zakat emerged as the dominant conceptual foundations of the literature, while newer themes such as blockchain, FinTech, sustainability, CSR integration, and digital accountability represent emerging research trajectories. Indonesia and Malaysia were identified as the leading contributors and primary collaboration hubs in the field. The study further demonstrates that zakat transparency has evolved from a narrow administrative concern into a multidimensional governance mechanism linked to institutional trust, stakeholder accountability, digital transformation, and social impact measurement. This research contributes by providing a comprehensive knowledge map that integrates fragmented discussions on governance, CSR, and zakat transparency and offers directions for future empirical and comparative studies in Islamic financial governance.